The Merger Mystery Why Spend Ever More on Mergers When So Many Fail? - Meeks, Geoff (Open Book Publishers, 2022)
Statistical studies over the last forty-five years show that, although there are success stories, very many mergers and acquisitions do not result in the increased operating profits that economics textbooks would lead one to expect. As consultancy McKinsey have put it, 'Anyone who has researched merger success rates knows that roughly 70% fail'. Yet-mysteriously-M&A activity has boomed across the globe, with a forty-fold increase in deals done each year now compared with four decades ago, in spite of the adverse general evidence. How can it be that talented, energetic, highly skilled, law-abiding, income-maximising participants in the M&A market will often promote mergers that lead to no operating gains, frequently with adverse effects on the wider economy too? Drawing on findings from a wealth of statistical analyses and case evidence from many businesses, the book presents answers to this merger mystery. In a synthesis of ideas from several disciplines, solutions are detected in misaligned incentives, distorted financial engineering and information asymmetry. By revealing how weaknesses at multiple points can interact and cumulate to produce inefficient outcomes, the discussion serves as a corrective to the overwhelmingly positive tone of most commentary on M&A, whilst also advocating changes in participants' contracts, in taxation, and in regulation which could significantly reduce the number of mergers that fail. Designed to be accessible to a wide readership, the book will be of interest to investors, to M&A practitioners and commentators, to researchers and students of economics, political economy, finance, management and accounting, and-importantly-to policy makers working in these areas.